A measure of modifiable lifestyle factors shaping subjective cognitive reserve in the general population - Moret-Tatay, Carmen; Tormos Muñoz, José María; Pascual-Leone, Alvaro (Frontiers in Psychology, 2024)
This study examined the psychometric properties of a newly developed scale for measuring Subjective Cognitive Reserve (SCR) across multiple domains, including Nutrition, Physical Condition, Sleep, Cognition, Willingness to Learn, Socialization, General Health, and Life Plan. The relationship between SCR scores and other established measures of cognitive reserve and subjective cognitive decline was also explored. A sample of 402 healthy participants aged 18 to 79 years took part in the study. The SCR scale demonstrated strong psychometric properties, including internal consistency and construct validity, supporting the theoretical model of perceived cognitive reserve. Convergent validity was confirmed through a positive correlation between SCR scores and resilience (BRCS) as well as with other cognitive reserve measures, indicating consistency in evaluating cognitive reserve across various instruments.Furthermore, discriminant validity was demonstrated by a significant negative correlation between SCR scores and subjective cognitive decline, suggesting that individuals with higher cognitive reserve experience lower levels of perceived cognitive decline. No significant relationship was found between SCR scores and chronological age, further supporting the construct validity of the scale by showing that cognitive reserve is influenced by dynamic factors beyond age. The findings highlight the potential of the SCR scale as a reliable and valid tool for assessing cognitive reserve and its protective role in cognitive health and well-being over time.